2015
DOI: 10.1002/2015gl064583
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Atlantic overturning increased by wind stress in climate models

Abstract: Previous Paleoclimate Model Intercomparison Project (PMIP) simulations of the Last Glacial Maximum (LGM) Atlantic Meridional Overturning Circulation (AMOC) showed dissimilar results on transports and structure. Here we analyze the most recent PMIP3 models, which show a consistent increase (on average by 41 ± 26%) and deepening (663 ± 550 m) of the AMOC with respect to preindustrial simulations, in contrast to some reconstructions from proxy data. Simulations run with the University of Victoria (UVic) ocean cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
158
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(188 citation statements)
references
References 35 publications
(52 reference statements)
30
158
0
Order By: Relevance
“…The PMIP3 ice sheets induced a strengthening and shoaling of the NADW cell in CCSM4 (compare experiments LGM and LGMCO 2 in Brady et al, 2013). In a recent study, Muglia and Schmittner (2015) found that applying glacial wind stress anomalies from the PMIP3 ensemble in the UVic model led to an increased northward salt transport, enhanced overturning and a deeper NADW cell, which is consistent with the ice-sheet effect in MPI-ESM. The sign of the GHG effect appears more robust.…”
Section: Overturningsupporting
confidence: 62%
See 2 more Smart Citations
“…The PMIP3 ice sheets induced a strengthening and shoaling of the NADW cell in CCSM4 (compare experiments LGM and LGMCO 2 in Brady et al, 2013). In a recent study, Muglia and Schmittner (2015) found that applying glacial wind stress anomalies from the PMIP3 ensemble in the UVic model led to an increased northward salt transport, enhanced overturning and a deeper NADW cell, which is consistent with the ice-sheet effect in MPI-ESM. The sign of the GHG effect appears more robust.…”
Section: Overturningsupporting
confidence: 62%
“…This inter-model spread was reduced in PMIP3, with most models simulating an increase in NADW strength and a deepening of the NADW cell (Muglia and Schmittner, 2015). The large inter-model spread in PMIP2 and the fact that most models fail to simulate the shoaling of the NADW cell in PMIP3 suggests that there is still a lack of understanding of the mechanisms that determine the glacial AMOC state.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in freshwater fluxes around Antarctica have also been argued to explain the high deep ocean stratification in a decoupled Community Earth System Model (CESM)1.1.2 ocean simulation under LGM boundary conditions (10). Many other coupled climate models, however, show different and widely diverging changes in the deep ocean circulation and stratification between preindustrial and LGM simulations (25,26). Possible reasons for this disagreement include differences between transient and fully equilibrated solutions (27,28), insufficient increase in Antarctic sea-ice cover and formation (29), and/or compensating effects due to other differences in the boundary conditions, such as changes in the ice sheets (26,30).…”
Section: Discussionmentioning
confidence: 99%
“…Many other coupled climate models, however, show different and widely diverging changes in the deep ocean circulation and stratification between preindustrial and LGM simulations (25,26). Possible reasons for this disagreement include differences between transient and fully equilibrated solutions (27,28), insufficient increase in Antarctic sea-ice cover and formation (29), and/or compensating effects due to other differences in the boundary conditions, such as changes in the ice sheets (26,30). A more detailed analysis of comprehensive LGM climate simulations is needed to better understand differences between them, but is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%